2016
DOI: 10.1016/j.jaci.2015.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA profiling reveals deregulated phosphatase and tensin homolog (PTEN)/phosphoinositide 3-kinase (PI3K)/Akt pathway in bronchial smooth muscle cells from asthmatic patients

Abstract: BSM cells of asthmatic patients are characterized by aberrant sncRNA expression that recapitulates multiple pathologic phenotypes of these cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 69 publications
2
22
0
Order By: Relevance
“…As observed for the CMC signatures, the pathway activation data (heatmap, Figure 2A ) also clearly distinguished between BSM cells of asthmatic and non-asthmatic subjects. In accord with our previous studies analysing small noncoding RNA expression patterns [ 21 ], the PTEN/AKT signalling system was again amongst the most affected ISPs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As observed for the CMC signatures, the pathway activation data (heatmap, Figure 2A ) also clearly distinguished between BSM cells of asthmatic and non-asthmatic subjects. In accord with our previous studies analysing small noncoding RNA expression patterns [ 21 ], the PTEN/AKT signalling system was again amongst the most affected ISPs.…”
Section: Discussionsupporting
confidence: 89%
“…We have hypothesized and provided evidence that the “primed” phenotype of asthmatic BSM cells is reflected in the signalling pathway signature of the cells. Using small RNA profiling we recently identified deregulated phosphatase and tensin homolog (PTEN)/phosphoinositide 3-kinase (PI3K)/Akt pathways in BSM cells of asthmatic patients as a candidate for a primed phenotype [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, 1 µg of each FFPE-or cell line-derived sample was used for sequencing library preparation using TruSeq Small RNA kit (Illumina Inc., San Diego, CA, USA) as previously described [26]. Each library was sequenced on HiSeq 2500 (Illumina Inc., San Diego, CA, USA) at a concentration of 10 pM for 50 cycles plus seven additional cycles for index sequencing in the single-read mode (1 × 50 base pairs).…”
Section: Sncrna Sequencing and Data Analysismentioning
confidence: 99%
“…As highly predicted miRNA targets, we considered only mRNAs characterized by a prediction score equal to 1 and identified by at least two out of four algorithms present in miRWalk database. For cell lines, differentially expressed mRNAs with |FC| ≥ 1.5 were considered as putative miRNA targets, taking into account both experimentally validated and highly predicted interactions, as done in our previous paper [26]. For the prediction of miRNA targets in TNBC tissues, publicly available RNA-seq data from the TCGA Breast Cancer dataset [25] were downloaded and all predicted miRNA-targeted RNAs were identified and taken into account, excluding transcripts that were not expressed in the tissues.…”
Section: Sncrna Sequencing and Data Analysismentioning
confidence: 99%
“…A large majority of these remain uncorrected or modestly corrected despite treatment with steroids [ 71 ]. Another recent study revealed that about 26 miRNAs are aberrantly expressed in the bronchial smooth muscle cells of asthmatic cells [ 72 ]. Besides, the target mRNAs of these aberrantly regulated miRNAs were found to play important roles in asthma pathogenesis in the form of cellular proliferation through phosphatase and tensin homolog and phosphoinositide 3-kinase/Akt signaling pathways.…”
Section: Epigenetic Mechanisms In Asthma: the Means To An Endmentioning
confidence: 99%